Inflammatory Cell Infiltration of Adrenals in COVID-19 - Zinserling, Vsevolod A.; Semenova, Natalya Yu.; Markov, Alexander G.; Rybalchenko, Oksana V.; Wang, Jun; Rodionov, Roman N.; Bornstein, Stefan R. (Hormone and Metabolic Research, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was originated in November–December 2019 in Wuhan, China, and has rapidly spread around the world causing severe health and socioeconomical damage to the entire civilization. The key feature of coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, is upper respiratory tract infection, which may be complicated by bilateral pneumonia. Angiotensin converting enzyme 2 (ACE2) has been identified as a key host factor, required for virus entry into cells. Interestingly, ACE2 is expressed not only in the respiratory system, but also in the other organs and systems including adrenal glands. Here we provide the first description of the pathomorphological changes in adrenal glands in patients with severe COVID-19 characterized by perivascular infiltration of CD3+ and CD8+ T-lymphocytes. Due to the central role of the adrenals in the stress response of the organism, this finding is of potential clinical relevance, because infection with the SARS-CoV-2 virus might critically impair adrenal function under pathophysiological conditions.
Keywords: ACE2; adrenal; infiltrations; COVID-19